Analysis and Development of Change Management Framework in Jatis Solutions - Febria, Dwina; Tjakraatmadja, Jann H; Welly, John (The Indonesian Journal of Business Administration, 2013)
The study aims to analyze change management implementation in Jatis Solutions and develop solutions to the finding issues to mitigate obstacles and accelerate the change stick. The company wanted to renew its business strategy and has announced it to the employees in Q4 2010. The organization was restructured, the business process also changed according to the new strategy. Turnover ratio was increased from 17% to 58% in 2011. A study conducted in 2012, analyzing the change implementation by comparing with Kotter’s 8-steps Change Management model. Realizing the change is stuck in removing obstacles and creating short term wins steps, the interconnection business elements of the current change was measured using 7S McKinsey to see the probable imbalance of elements which might be the core obstacles to the change. The initiatives execution then measured using DICE methodology to understand the obstacles on winning the short terms. Improvements to change programs are proposed by preparing readiness for change to managers and employees motivation programs. Keywords: Change Management, IT Delivery Service, Kotter’s 8 Leading Step of Change, 7S McKinsey, DICE methodology